(untitled) (Pedagogy of Higher and Secondary Education, 2009)
Criteria of evaluation of knowledges and abilities for the plastanatomii students of artistic specialties in the context of the credit-module departmental teaching a question is examined about the improvement of educational process on employments on plastanatomii accordingly innovative changes in the modem system of formation of Ukraine, and also an attempt to create clear and high-quality description of criteria of evaluation of knowledge and abilities of students on specdiscipline is conducted.